Die verhouding tussen Ou-Testamentiese wetenskap en Teologiese interpretasie van die Bybel: Handelinge 8:26–40 as gevallestudie - Viljoen, Anneke (HTS teologiese studies, 2017)
Theological interpretation of the Bible represents a broadening of the hermeneutical approaches available to an interpreter of Bible texts. As such, Theological interpretation of the Bible opens up the possibility to investigate and explore more aspects of the Bible text. Especially aspects that are in line with the nature of the Bible text such as Scriptures of the church as well as the illocutionary force of these texts. After a few introductory remarks concerning Theological interpretation of the Bible, three questions guided reflection on defining theological interpretation: first, Why Theological interpretation of the Bible?; second, What is Theological interpretation of the Bible not?; and third, What is Theological interpretation of the Bible? Last mentioned was explored on the basis of a focus text, namely Acts 8:26–40 that served as a case study.